1992
DOI: 10.1246/bcsj.65.2475
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Chemiluminescence Properties of 6-(4-Methoxyphenyl)-2-methylimidazo[1,2-a]pyrazin-3(7H)-one and 2-Methyl-6-(2-naphthyl)imidazo[1,2-a]pyrazin-3(7H)-one

Abstract: New Cypridina luciferin analogues, 6-(4-methoxyphenyl)-2-methylimidazo[1,2-a]pyrazin-3(7H)-one (MCLA) and 2-methyl-6-(2-naphthyl)imidazo[1,2-a]pyrazin-3(7H)-one (NCLA), were prepared together with their oxyluciferin analogues, 2-acetamido-5-(4-methoxyphenyl)pyrazine (MCOLA) and 2-acetamido-5-(2-naphthyl)pyrazine (NCOLA). Various chemiluminescence properties of these compounds were compared with those of known luciferin analogues, 2-methyl-6-phenylimidazo[1,2-a]pyrazin-3(7H)-one (CLA) and 6-(3-indolyl)-2-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The result showed that the maximum emission wavelength was 460 nm (see Fig. 5), which was equal to the emission maximum of chemiluminescence of MCLA [1]. The results indicated that the ECL of MCLA was similar to its chemiluminescence.…”
Section: The Ecl Spectrummentioning
confidence: 73%
See 1 more Smart Citation
“…The result showed that the maximum emission wavelength was 460 nm (see Fig. 5), which was equal to the emission maximum of chemiluminescence of MCLA [1]. The results indicated that the ECL of MCLA was similar to its chemiluminescence.…”
Section: The Ecl Spectrummentioning
confidence: 73%
“…6-(4-Methoxyphenyl)-2-methylimidazo[1,2-a]pyrazin-3(7H)-one (MCLA) is one of the analogues of Cypridina hilgendorfii luciferin, and has been prepared by Goto and co-workers as chemiluminescent compound that exhibits chemiluminescence in aqueous solutions [1]. Its molecule structure is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…During these investigations, it was revealed that 1a reacts with triplet oxygen in aqueous solutions to generate a neutral singlet excited-state amide molecule 2a*, as shown in Scheme 1. A comparable chemiluminescence mechanism has been described for a reaction with superoxide anion in an aqueous solution (6). In general, the overall chemiluminescence efficiency is dependent on: (a) emitter-formation efficiency; (b) singlet excited-state formation efficiency; and (c) fluor- escence efficiency of the emitter, such as 2a*.…”
Section: Introductionmentioning
confidence: 85%
“…Goto et al have developed Cypridina luciferin analogues, 2-methyl-6-phenylimidazo[1,2-a]pyrazin-3(7H)-one (CLA) (3,5) and 2-methyl-6-(4methoxyphenyl)imidazo [1,2-a]pyrazin-3(7H)-one (1a; MCLA; Figure 1) (6), as chemiluminescence probes, which were shown to emit light in aqueous solutions. The chemiluminescence efficiency of MCLA in acetate buffer in the presence of superoxide anion is about 1.3 times greater than that of CLA (6) and, therefore, the MCLA chemiluminescence method in aqueous solutions is widely utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Since the use of 2-methyl-6-phenylimidazo [1,2-a] pyrazin-3(7H)-one (CLA) 1 (1) for the detection of superoxide anions was first reported, various imidazopyrazinone-type chemiluminescent probes have been developed (2)(3)(4)(5)(6)(7). One such probe, 2-methyl-6-(4-methoxyphenyl)imidazo[1,2-a] pyrazin-3(7H)-one (MCLA) (1; Fig.…”
Section: Introductionmentioning
confidence: 99%